Pengaruh Kesempatan Kerja, Tingkat Pengangguran Terbuka dan Pendidikan terhadap Kemiskinan di Provinsi Kalimantan Selatan Periode 2008-2022 - Wahidah, Wahidah; Saleh, Muhammad (PPJP ULM, 2025)
The purpose of this study was to determine the relationship between the dependent variable of poverty in South Kalimantan province, with the independent variable of employment opportunities, open unemployment rate and education. The data source is a time series covering the years 2008-2022 using multiple linear regression analysis. Based on the findings of the study, employment opportunities do not affect poverty partially, but the level of open unemployment and education affect poverty. In South Kalimantan province, there is a simultaneous influence on poverty between variables of employment opportunities, open unemployment rate and education.